Q: solve for x (show steps) 4( x – 2 ) = 5( x + 3)

A: 4( x - 2 ) = 5( x + 3) (4)(x)+(4)( - 2)=(5)(x)+(5)(3) 4x - 8 = 5x + 15 4x - 8 = 15 - 5x - x - 8 = 15 - x = 15 + 8 - x = 23 x = 23/-1 x = - 23

Question

Asked 2/9/2012 5:54:04 PM

Updated 87 days ago|3/26/2018 3:45:04 AM

1 Answer/Comment

Edited by jeifunk [3/26/2018 3:45:04 AM]

Rating

3

4( x - 2 ) = 5( x + 3)

(4)(x)+(4)( - 2)=(5)(x)+(5)(3)

4x - 8 = 5x + 15

4x - 8 = 15 - 5x

- x - 8 = 15

- x = 15 + 8

- x = 23

x = 23/-1

x = - 23

(4)(x)+(4)( - 2)=(5)(x)+(5)(3)

4x - 8 = 5x + 15

4x - 8 = 15 - 5x

- x - 8 = 15

- x = 15 + 8

- x = 23

x = 23/-1

x = - 23

Added 87 days ago|3/26/2018 3:45:00 AM

This answer has been confirmed as correct and helpful.

solve for x: show steps 8x + 4 = 4x – 4 **Weegy:** 8x + 4 = 4x - 4
8x - 4x = - 4 - 4
4x = - 8
x = - 8/4
x = - 2 (More)

Question

Expert Answered

Updated 4/15/2014 1:50:22 PM

0 Answers/Comments

solve for x with steps 4x – 4 + 3x = 3x + 5 – 5x **Weegy:** 4x+3x-4=3x-5x+5
7x-4=-2x+5
7x+2x=5+4
9x=9
x=9/9
x=1
(More)

Question

Expert Answered

Updated 157 days ago|1/14/2018 4:01:28 PM

0 Answers/Comments

solve for x with steps 4( x – 2 ) = 5( x + 3) **Weegy:** 9x (More)

Question

Expert Answered

Updated 4/15/2014 1:49:31 PM

2 Answers/Comments

4( x – 2 ) = 5( x + 3);

4x-8 = 5x+15;

4x - 5x = 15 + 8;

-x = 23;

x = -23

4x-8 = 5x+15;

4x - 5x = 15 + 8;

-x = 23;

x = -23

Added 4/15/2014 1:49:31 PM

This answer has been confirmed as correct and helpful.

solve for x (show steps)4( x – 2 ) = 5( x + 3) **Weegy:**
4( x – 2 ) = 5( x + 3);
4x - 8 = 5x + 15;
4x - 5x = 15 + 8;
-x = 23;
x = -23
(More)

Question

Expert Answered

Updated 7/28/2014 1:05:54 PM

0 Answers/Comments

27,006,301 questions answered

There are no comments.